The conceptual fields theory and its role in Mathematics Education - Alfaro-Carvajal, Cristian (2016)
This article refers to the theory of Vergnaud’s conceptual fields and its implications in teaching mathematics. Fundamental concepts of this theory are discussed in light of teaching and learning mathematics; providing specific examples in the discipline and establishing relationship with other related references; for example, Polya problem-solving and Brousseau didactic situations, among others.